THE DISCOVERY OF REGISTERS IN ENGLISH NEWSPAPER OF BALI TRAVEL NEWS - Dewi, Ni Luh Eka Trisna; Pratiwi, Desak Putu Eka; Jayantini, IGA Sri Rwa (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTThis study aims to discuss the discovery of registers in the newsletter Bali Travel Newsaccording to Biber and Conrad theory (2009) which states that registers are variationsrelated to certain usage situations. The existence of newspapers in the form of printedmedia is still in great demand by the public. This newspaper is written in English andcontains articles that do occur in tourism in Bali without age restrictions to readers. Ingeneral, newspapers often used informal words rather than formal words according totheir lexical and grammatical characteristics which are very interesting and entertaining.The register description includes three main components: context of situation, linguisticfeatures, and functional interpretation between the first and two components. The data isanalyzed with descriptive qualitative method. Linguistic features included word selectionsuch as the use of pronouns, lexical and active as well as passive voice. Results arepresented through formal and informal methods.Keywords: register, context of situation, linguistic features.ABSTRAKPenelitian ini bermaksud untuk membahas temuan register pada surat kabar Bali TravelNews menurut teori Biber dan Conrad (2009) yang menyatakan bahwa register adalahvariasi yang berkaitan dengan situasi penggunaan tertentu. Keberadaan surat kabardalam bentuk media cetak masih banyak diminati oleh masyarakat. Koran inimenggunakan bahasa Inggris dan berisi artikel yang terjadi di Pariwisata di Bali tanpaadanya batasan umur bagi pembacanya. Pada umumnya, surat kabar lebih seringmenggunakan kata-kata informal daripada kata-kata formal sesuai dengan ciri leksikaldan gramatikal yang sangat menarik dan menghibur. Deskripsi register mencakup tigakomponen utama: konteks situasi, fitur linguistik, dan interpretasi fungsional antarakomponen pertama dan dua. Itu dianalisis dengan metode deskriptif kualitatif. Cirikebahasaan termasuk pemilihan kata seperti penggunaan kata ganti, leksikal dan aktifserta suara pasif. Hasil disajikan melalui metode formal dan informal.Kata kunci: register, konteks situasi, ciri kebahasaan